RELIGION AND REGULATION IN INDONESIA - Nurhartanto, Gregorius Sri (Indonesia Law Review, 2017)
The book “Religion and Regulation in Indonesia” written by Ismatu Ropi is very interesting because it can envisage the religious life and its regulation in Indonesia completely, starting from the period before Indonesia independence until present. This book analyses the state regulation on religious affairs in modern Indonesia, focusing on understanding its history and consequences to citizen’s religious life.